Design of a Tourist Communication Plan that Shows the Matrilineal Cultural Heritage of the Bribri People (Talamanca, Costa Rica) - Alonso López, Nadia (2022)
This research develops a tourism communication plan for the indigenous Bribri community. The main objectives of the plan are to attract quality tourism by showcasing the intangible cultural heritage of the Bribi and so help preserve their culture. We use an analytical-descriptive methodology based on an analysis of the environment and a definition of actions through participatory processes with the community. These processes are oriented towards the empowerment of indigenous women. The Bribri live in the canton of Talamanca (Costa Rica). The Bribi and other ethnic groups in the area can be distinguished from neighbouring communities because they have a matrilineal social structure, and their economies are based on farming – to which has been added an incipient tourism. To enhance the durability of their cultural heritage, various actions are being implemented by the Bribri in collaboration with the Universitat Politècnica de València (UPV) and the Instituto Tecnológico de Costa Rica (TEC). These actions include the development of this communications plan – which aims to preserve the imprint of Bribri culture and develop a method that can be used by other indigenous communities with similar characteristics.